Answer: ![y=\frac{1}{4}x-3](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B1%7D%7B4%7Dx-3)
Step-by-step explanation:
- The equation of the line in the slope intercept form is: ![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
Where m is the slope and b is the y-intercept of the line
- Let's choose two points of the line: (8,-1) and (-4,-4).
- You must calculate the slope of the line as following:
![m=\frac{y_2-y_1}{x_2-x_1}=\frac{-4-(-1)}{-4-8}=\frac{1}{4}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D%3D%5Cfrac%7B-4-%28-1%29%7D%7B-4-8%7D%3D%5Cfrac%7B1%7D%7B4%7D)
- As you can see in the graph attached, the line intersects the y-axis at -3, then b=-3.
- Substituting values into the equation of the line, you obtain:
![y=\frac{1}{4}x-3](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B1%7D%7B4%7Dx-3)
Answer:
Class interval 10-19 20-29 30-39 40-49 50-59
cumulative frequency 10 24 41 48 50
cumulative relative frequency 0.2 0.48 0.82 0.96 1
Step-by-step explanation:
1.
We are given the frequency of each class interval and we have to find the respective cumulative frequency and cumulative relative frequency.
Cumulative frequency
10
10+14=24
14+17=41
41+7=48
48+2=50
sum of frequencies is 50 so the relative frequency is f/50.
Relative frequency
10/50=0.2
14/50=0.28
17/50=0.34
7/50=0.14
2/50=0.04
Cumulative relative frequency
0.2
0.2+0.28=0.48
0.48+0.34=0.82
0.82+0.14=0.96
0.96+0.04=1
The cumulative relative frequency is calculated using relative frequency.
Relative frequency is calculated by dividing the respective frequency to the sum of frequency.
The cumulative frequency is calculated by adding the frequency of respective class to the sum of frequencies of previous classes.
The cumulative relative frequency is calculated by adding the relative frequency of respective class to the sum of relative frequencies of previous classes.
Answer:
In the pictures below
Step-by-step explanation:
Answer:
m is -12/7 and b is -64/7
Step-by-step explanation:
Use rise over run (change in y / change in x) to find the slope, m:
(-4 - 8) / (-3 + 10)
= -12/7
So, m is -12/7.
Plug in this value and a point into y = mx + b, then solve for b:
y = mx + b
-4 = -12/7(-3) + b
-4 = 36/7 + b
-64/7 = b
So, m is -12/7 and b is -64/7